We need to start thinking about promoting the demand, uptake, and equitable distribution of COVID-19 vaccines NOW! - Derrick Bary Abila; Sharon D. Dei-Tumi; Fabrice Humura; Godwin N. Aja (Elsevier, 2020)
SARS-CoV-2 (COVID-19) is spreading rapidly within countries around the world, thus necessitating the World Health Organisation (WHO) to project that the peak of the pandemic has not been reached yet. Globally, COVID-19 public health control measures are being implemented; however, promising COVID-19 vaccine candidates are still in the early-stage clinical trials.Judging from previous vaccine programs around the world and the challenges encountered in the distribution and uptake, there seems to be no guarantee that there will be widespread acceptance and equitable distribution of the new COVID-19 vaccines when they are approved for use.Therefore, there is an urgent need to start engaging the public to allay their fears and misconceptions with the view to building trust and promoting acceptance and ultimately achieving a potential impact in controlling the pandemic. Borrowing from previously used successful public health strategies, including the application of the health belief model to engage communities, can go a long way in promoting the demand, uptake, and equitable distribution of the COVID-19 vaccine, thereby minimizing the likelihood of vaccine hesitancy.